Automated 3-D optic disk reconstruction and feature extraction for glaucoma analysis - Xu, Juan (2008)
Color fundus image processing is a challenging research topic in medical image processing. The visualization and parameter estimation of the optic disk, one of the main components on fundus image, is investigated in this research. Computer-aided processing for the measurement of optic disk boundary and its three dimensional (3-D) shape not only provides more clinical information which is difficult to be obtained manually, but also relieves the clinicians from time-consuming workloads.